STAD Model Assisted by Islamic Animated Videos to Enhance Junior High Students’ Religious Character - Khairunnisa Khairunnisa; Umi Hijriyah; Ais Isti'ana (MAN 4 Kota Pekanbaru, 2026)
This study examines the strengthening of students’ religious character through integrative and collaborative innovations in Islamic Religious Education (IRE) learning. The primary issue identified is the suboptimal development of religious character indicators, particularly in the dimension of obedience in worship, resulting from the predominance of cognitively oriented instruction that insufficiently engages students in active learning processes. This research analyzes the effectiveness of implementing the cooperative learning model of the Student Teams Achievement Division (STAD) type assisted by Islamic animated videos in enhancing students’ religious character values at SMP Negeri 31 Bandar Lampung. Employing a quantitative approach with a quasi-experimental design, the study involved both experimental and control classes. The analysis yielded a significance value of 0.007 (< 0.05), indicating a statistically significant difference between the two groups. These findings affirm that the integration of STAD and Islamic animated videos is effective in strengthening religious character in an active, contextual, and sustainable manner.